66‐3: Micro‐LED Display with Simultaneous Visible Light Communication Function. Issue 1 (30th May 2018) - Li, Xianbo; Cho, Wai Keung; Hussain, Babar; Kwok, Hoi Sing; Yue, Chik Patrick
Abstract : The first real‐time micro‐LED (µLED) display with simultaneous visible light communication (VLC) function for text message broadcast based on a 400×240 blue µLED array is presented, demonstrating the great potential of enabling various displays using VLC technologies for futuristic IoT applications. Transmitted messages are detected and shown on an LCD.